Estimated Dose of Electrons Emitted from Radon-222 Progenies Applying Variance Reduction Methods in ORNL Phantom - Sh Banari Bahnamiri; S. H Miri Hakimabad; R Izadi Najafabadi (مجله علوم و فنون هسته‌ای, 2013)
Radon is the main source of radioactivity in the environment. Scientific investigations revealed that after the smoking, radon ranked as the second cause of lung cancer. Despite the short half life of Radon-222, it is produced continuously in nature, as its main source is the decay of uranium-238 with the half life time of 4.5×109 years. Radon exists in air, mines, oil, natural gas, building materials and groundwater; therefore it may easily enter the lung through the inspiratory system and emits alpha, beta, gamma, X-ray and conversion electron. These particles and radiations which can deposit their energies in different organs are considered to be very harmful for the human health. Although, many houses have been built on a bed of granite rock, the exact assessment for the amount of radon in the residential houses has not yet been carried out. In this regard, a serious analysis is needed to be made in this field, in particular, for calculation of different organs' absorbed dose of Radon and its progenies. In this study, Monte Carlo calculations have been made using MCNPX2.4.0 code and the variance reduction methods were applied for the calculations of the absorbed dose due to beta particle and the conversion electron from decay of Radon and its progenies. An effective dose rate of 5.93 µSvWLM-1 in this respect has been evaluated for the human body.